Identify metabolism-related genes IDO1, ALDH2, NCOA2, SLC7A5, SLC3A2, LDHB, and HPRT1 as potential prognostic markers and correlate with immune infiltrates in head and neck squamous cell carcinoma - Li, Ce; Chen, Shuai; Jia, Wenming; Li, Wenming; Wei, Dongmin; Cao, Shengda; Qian, Ye; Guan, Rui; Liu, Heng; Lei, Dapeng (Frontiers in Immunology, 2022)
Hypopharyngeal squamous cell carcinoma (HSCC) is a kind of head and neck squamous cell carcinoma (HNSCC) with poor prognosis. Metabolic reprogramming may regulate the tumor microenvironment (TME) by adapting quickly to cellular stress and regulating immune response, but its role in HSCC has not been reported. We used the nCounter® Metabolic Pathways Panel to investigate metabolic reprogramming, cellular stress and their relationship in hypopharyngeal squamous cell carcinoma tissues and adjacent normal tissues. Metabolism-related pathways Nucleotide synthesis and Glycolysis pathways were significantly up-regulated, while Amino acid synthesis and Fatty acid oxidation pathways were significantly down-regulated in HSCC tissues compared to adjacent normal tissues. There is a significant correlation between Metabolism-related pathways and cellular stress pathways. Enrichment of immune cells and Tumor Infiltrating Lymphocytes (TILs) analysis showed changes of immune responses between HSCC tissues and adjacent normal tissues. Overall survival analysis showed up-regulated genes CD276, LDHB, SLC3A2, EGFR, SLC7A5 and HPRT1 are potential unfavorable prognostic markers in HNSCC, while down-regulated genes EEA1, IDO1, NCOA2, REST, CCL19 and ALDH2 are potential favorable prognostic markers in HNSCC. Moreover, metabolism-related genes IDO1, ALDH2, NCOA2, SLC7A5, SLC3A2, LDHB and HPRT1 are correlated with immune infiltrates in HNSCC. These results suggest metabolic reprogramming occurs and correlates with cellular stress and immune response in HSCC, which may help researchers understand mechanisms of metabolic reprogramming and develop effective immunotherapeutic strategies in HNSCC.